Pendampingan Penguatan Kurikulum Madrasah Diniyah dalam Meningkatan Kualitas Generasi Millenial - Makmun, A. Rodli; Muhsin, M.; Khambali, Khambali (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
Early education has an important role in forming a quality millennial generation. The quality of early education can be seen from the curriculum implemented. A quality Diniyah curriculum enables the millennial generation to understand religion and its practice in everyday life. This mentoring program was carried out with the aim of describing the existence of the Madrasah Diniyah curriculum. Furthermore, curriculum development was carried out as an effort to prepare a quality millennial generation. The mentoring method uses Participatory Action Research. This method is used in the context of community service research in designing the development of the Madrasah Diniyah curriculum. Curriculum development strengthens aspects of the Arabic language, especially the ability to understand grammar. The media and learning methods used adapt modern methods and maintain classical methods as